Penerapan Six Sigma untuk Pengendalian Kualitas Keripik Singkong Di IKM Gazal Makmur - Kurniawati, Elly; Agustiningtyas, Dwi Wahyu; Kusumasari, Findi Citra (Politeknik Negeri Jember, 2024)
The purpose of this research was to determine the quality control of cassava chips at IKM Gazal Makmur located in the Kotaanyar sub-district, Probolinggo. There were several findings of the type of defect which also became the reason why this research was carried out. The types of defects found consisted of burnt products, crushed products and product defects in the form of scraps. This research uses the Six Sigma method with the DMAIC Define, Measure, Analyze approach, and is limited to the Improve stage. The results show that the most types of defects are in the cassava chips production process. There were product defects in the form of 67.2% remaining pieces, 19.0% crushed chips and 13.8% burnt chips. Based on the calculation of the final yield, the results of the analysis are 82.7% for frying, 76.2% for packaging and 15.7% for chopping. The results of the analysis of the causes of product defects are damage due to unsharp blades and careless handling when inserting the product.